Health-related and sociodemographic factors associated with physical frailty among older cancer survivors. Issue 1 (January 2021) - Koll, Thuy T.; Semin, Jessica N.; Brodsky, Rachel; Keehn, Daina; Fisher, Alfred L.; High, Robin; Beadle, Janelle N.
Abstract: Objective: The purpose of this study was to examine factors associated with frailty in older cancer survivors. Materials and methods: This is a cross-sectional study using data from the National Social Health and Aging Project (NSHAP) Wave 2, and includes an in-home, nationally representative sample of community-dwelling adults ≥50 years and older from the United States. Frailty score was computed for each individual using a modified 4-point scale based on the phenotypic frailty. Ordinal logistic regression was used to characterize the association between health-related, sociodemographic factors and frailty. Results: Among the 3377 participants, 461 were cancer survivors (answered "yes" to "ever have cancer other than skin cancer"). A final sample of 394 cancer survivors were included: 59 participants (16.1%) were frail, 219 participants were pre-frail (59.8%), and 88 participants were non-frail (24.0%). The univariate analyses showed increasing age (OR 1.48; CI 1.29–1.72; p -value <.001), comorbidities (OR 1.43; CI 1.25–1.64; p-value <.001), depression (OR 1.27; CI 1.19–1.35; p-value <.001) and low mobility (OR 1.55; CI 1.37–1.78; p-value <.001) were associated with frailty. Participants with high self-rated (good/very good/ excellent) physical health (OR 0.18; CI 0.11–0.30; p < .001) and mental health (OR 0.27; CI 0.15–0.50; p < .001) were less likely to be frail. In a multivariate model, frailty was associated with age, self-rated physical health, depression, ability to perform activities of daily living, and mobility ( p < .05). Conclusion: The findings highlight the importance of incorporating geriatric assessment into cancer survivorship to prevent and delay the progression of frailty.